An edition with commentary of the Batrachomyomachia - Hosty, M (2013)
The thesis consists of three main sections: the Introduction, the text (with apparatus), and the Commentary. The Introduction begins with a survey of the available evidence for the poem’s date and authorship, before moving on to consider its generic affiliations and influences, focusing on two particular areas: its links with the ill-defined genre of παρῳδία, and its relationship to animal-narratives elsewhere in ancient literature (particularly fable) and visual art. This is followed by a detailed analysis of the poem’s style and metre, a brief tour of its Nachleben up to the 13th century, and a summary of the notoriously tangled manuscript tradition. The text is new, and differs substantially from both that of Allen (in the OCT) and of West (the most recent English edition). The apparatus, as explained in more detail on p. 117, is somewhere between the two: it takes into account the readings of only nine MSS from the 80-100 extant, and does not attempt to represent every single textual variation even among these nine, but it is much fuller than the minimalist apparatus of the Loeb. It aims to provide a useful source for scholars interested in the poem’s many and serious textual cruces, while remaining more succinct and user-friendly than the dense and sometimes baffling apparatus of Ludwich’s monumental 1896 edition. The text is followed by an English prose translation: this makes no claims to beauty, and is simply intended as a relatively literal guide to the sense of the Greek. The Commentary, finally, is twofold. Any commentary on the Batrachomyomachia will inevitably spend much space and ink on purely textual issues, and on the fundamental task of unearthing meaning from the dizzying range of wild and nonsensical variants available. Interspersed with these textual points, however, this commentary includes considerations of the poem not as a mechanics problem but as a sophisticated Hellenistic work of art – exploring its intertextualities, its characterisation, its dramatic effects, its dry sense of humour, and subjecting it to the serious literary analysis it has often been denied.